A fast-hardening early-strength high-ductility cement-based composite material, a preparation method and application thereof

CN122977803APending Publication Date: 2026-10-27CHINA RAILWAY DESIGN GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611477414.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

在拉应力或弯应力作用下,该类材料极易发生开裂,且裂缝一旦产生,其裂缝宽度会随荷载持续增大而扩展,无法有效控制

Benefits of technology

1.本发明采用快硬硫铝酸盐水泥与普通硅酸盐水泥组成的复合胶凝体系,作为修补材料强度发展的主要来源。其中,硫铝酸盐水泥水化反应快,可较早形成钙矾石等水化产物,有利于快速建立早期强度;普通硅酸盐水泥水化形成水化硅酸钙凝胶和氢氧化钙等水化产物,可在中后期持续参与结构形成和强度发展,二者复合有利于兼顾材料的早期强度和后期强度稳定性。粉煤灰用于优化颗粒级配、改善浆体工作性及硬化体微结构,在控制掺量的条件下兼顾工作性能与早期强度发展。文石型碳酸钙粉通过微填充、异相成核及颗粒级配优化作用促进基体结构致密化,其针状或棒状颗粒还可对裂纹扩展产生阻滞和偏转作用。经钛酸酯偶联剂改性后,文石型碳酸钙粉的分散性及与水泥浆体的界面相容性得到改善,有利于其均匀分布并充分发挥微填充和成核作用。聚乙烯纤维经表面活化及硅烷偶联改性后,表面极性和亲水性提高,可改善纤维在水泥基浆体中的润湿、分散及界面黏结,使纤维能够通过跨缝桥联、拔出滑移及拉伸变形发挥耗能作用。聚醚改性有机硅消泡剂则通过有机硅链段的低表面张力和聚醚链段的水相分散作用,对拌合过程中形成的气泡进行破泡和抑泡,减少硬化体中的大孔和连通孔缺陷,提高基体密实度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977803A_ABST
    Figure CN122977803A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of urban rail transit structure maintenance, in particular to a fast-hardening early-strength high-ductility cement-based composite material, a preparation method and application, the cement-based composite material comprising a sulphoaluminate cement, a common portland cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, a retarder, a thickener, a modified defoaming agent, a water reducing agent, a shrinkage reducing agent and an expansive agent; the modified aragonite-type calcium carbonate powder is titanium ester coupling agent modified aragonite-type calcium carbonate powder; the modified fiber is a silane coupling agent modified polyethylene fiber with hydroxyl and amino groups; and the modified defoaming agent is a polyether modified organic silicon defoaming agent. The cement-based composite material can realize rapid repair of damaged parts of the rail transit structure during the maintenance window, and the matrix after repair of the composite material has better ductility and supporting strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of urban rail transit structure maintenance technology, and in particular to a fast-hardening, early-strength, high-ductility cement-based composite material, its preparation method, and its application. Background Technology

[0002] High-speed rail and subway systems have extremely high requirements for the smoothness and safety of their track structures, and their operation and maintenance windows are extremely limited, typically only about four hours at night. Therefore, when local damage occurs to the rail transit structure, there is an urgent need for a material that can be repaired and restored to operation in a short time.

[0003] Currently, the traditional cement-based materials widely used in rail transit structure repair projects are mainly fast-hardening and early-strength types, whose core advantage lies in their rapid development of mechanical strength. For example, the compressive strength of this type of material can reach more than 15MPa within 2 hours after construction, and more than 20MPa within 1 day, which can better meet the urgent need for early strength during "maintenance window" construction.

[0004] However, these traditional repair materials have significant technical drawbacks. During service, rail transit structures are subjected to the coupled effects of multiple factors, including temperature cycling, foundation settlement, and train reciprocating loads. The repaired area must simultaneously withstand various complex internal forces such as tension, compression, bending, shear, and torsion. While traditional repair materials possess high compressive strength, their tensile strength, flexural strength, crack resistance, ductility, and toughness are all relatively low, classifying them as typical quasi-brittle materials. Under tensile or flexural stress, these materials are highly prone to cracking, and once cracks appear, their width expands continuously with increasing load, making effective control impossible. Crack propagation not only weakens the reinforcement effect of the repair layer but also provides a penetration channel for corrosive media (such as chloride ions, water, and carbon dioxide), accelerating steel corrosion and interface delamination, severely shortening the service life of the repaired structure. Furthermore, traditional repair materials generally have a high modulus of elasticity. When temperature changes or foundation settlement cause structural deformation, significant constraint stress will be generated within the repair layer, further exacerbating damage accumulation and reducing the long-term service reliability of the structure.

[0005] Given this practical need, there is an urgent need to develop a new type of material for repairing rail transit structures. The core idea is to simultaneously improve the ductility and toughness of the repair material while achieving rapid hardening and early strength. This will enable efficient and rapid repair of structural damage within a limited maintenance window without sacrificing the material's deformation capacity, thus providing reliable material support for the safe operation and efficient maintenance of rail transit structures. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a fast-hardening, early-strength, high-ductility cement-based composite material, its preparation method, and its application. The cement-based composite material of this invention enables rapid repair of damaged areas in traffic structures during maintenance windows, and the repaired matrix exhibits better ductility and support strength.

[0007] This invention provides a rapid-hardening, early-strength, and high-ductility cement-based composite material. The cement-based composite material comprises sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expanding agent. By weight, the ratio of sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expanding agent is (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 parts): (2.4-2.6 parts): (5.4-5.6 parts): (8-12 servings): (68-72 servings); The modified aragonite-type calcium carbonate powder is a titanate coupling agent modified aragonite-type calcium carbonate powder. The modified fiber is a polyethylene fiber modified with a silane coupling agent containing hydroxyl and amino groups; The modified defoamer is a polyether-modified silicone defoamer.

[0008] Furthermore, the sulfoaluminate cement is a rapid-hardening sulfoaluminate cement with a strength grade of 52.5 (label P.O52.5 rapid-hardening sulfoaluminate cement).

[0009] Furthermore, the ordinary silicate cement is ordinary silicate cement with a strength grade of 42.5 (P.O42.5 cement) or 52.5 (P.O52.5 cement).

[0010] Furthermore, the fly ash is Grade I fly ash.

[0011] Furthermore, the preparation method of the titanate coupling agent modified aragonite calcium carbonate powder is as follows: aragonite calcium carbonate powder with a water content of less than 0.5% is added to an ethanol solution to prepare a slurry with a solid content of 40%-60%; anhydrous ethanol containing titanate coupling agent is added to the slurry and mixed evenly; the mixture is stirred for 30 min-90 min at 40℃-60℃ and a rotation speed of 1000 r / min-3000 r / min; the mixture is dried at 80℃-110℃, depolymerized, and sieved to obtain the titanate coupling agent modified aragonite calcium carbonate powder.

[0012] Furthermore, aragonite-type calcium carbonate powder with a moisture content of less than 0.5% can be obtained by drying the powder at 80℃-110℃, or it can be purchased.

[0013] Furthermore, in this invention, depolymerization is achieved by physically dispersing the titanate coupling agent-modified aragonite-type calcium carbonate powder, thereby preventing its agglomeration.

[0014] Furthermore, in this invention, technicians can select the particle size of the titanate coupling agent-modified aragonite-type calcium carbonate powder according to actual needs, which is achieved by sieving.

[0015] Furthermore, in the ethanol solution, which is a mixed solvent composed of anhydrous ethanol and deionized water, the ratio of anhydrous ethanol to deionized water by volume is (4-9):1.

[0016] Furthermore, by mass, the ratio of the titanate coupling agent to anhydrous ethanol is 1:(5-10).

[0017] Furthermore, the mass ratio of the titanate coupling agent to the aragonite-type calcium carbonate powder is 1%.

[0018] Furthermore, the titanate coupling agent includes one or more of isopropyl tris(dioctylphosphoyloxy) titanate and isopropyl tris(dioctylphosphoyloxy) titanate.

[0019] Furthermore, the aragonite-type calcium carbonate powder has a CaCO3 content of ≥95%, an average particle size of 5μm-15μm, a specific surface area of ​​≥500m² / kg, and a crystal structure of needle-like or rod-like.

[0020] Furthermore, the quartz sand is quartz sand with a particle size of 100-170 mesh.

[0021] Furthermore, the preparation method of the silane coupling agent modified polyethylene fiber with hydroxyl and amino groups is as follows: the surface of the polyethylene fiber is activated, and the activated polyethylene fiber is immersed in an ethanol aqueous solution containing silane coupling agent, wherein the mass concentration of silane coupling agent in the ethanol aqueous solution is 1%-5%; the pH value of the system is adjusted to 4-5 with acetic acid, and the fiber is allowed to stand for hydrolysis for 20-60 minutes, followed by immersion at 20℃-40℃ for 30-120 minutes, during which stirring is required; the fiber is then washed with anhydrous ethanol and deionized water in sequence, and dried at 50℃-80℃.

[0022] In this invention, hydroxyl groups are first formed on the surface of polyethylene fibers through activation. Under a weakly acidic environment, the alkoxy groups of the silane coupling agent undergo hydrolysis, gradually removing the alkoxy groups and generating a large number of silanol groups (-Si-OH), thus completing the hydrolysis activation. This process, involving static hydrolysis for 20-60 minutes, ensures complete hydrolysis of the silane while effectively preventing excessive self-polymerization and precipitation of silane molecules. After hydrolysis, under constant temperature stirring impregnation conditions at 20℃-40℃, silane molecules with silanol groups are uniformly impregnated on the surface of the polyethylene fibers. The hydroxyl groups on the fiber surface and the silanol groups of the silane molecules first form preliminary physical adsorption through intermolecular hydrogen bonds, achieving uniform loading of silane molecules on the fiber surface. Finally, during drying at 50℃-80℃, the hydroxyl groups on the fiber surface and the silane silanol groups undergo dehydration condensation reactions to form stable Si-OC covalent bonds, thereby realizing silane coupling agent-modified polyethylene fibers with hydroxyl and amino groups.

[0023] In this invention, after modification with the above-mentioned silane coupling agent, polar amino and hydroxyl groups are introduced into the polyethylene fiber, which significantly improves the hydrophilicity of the fiber surface. This not only enhances the interfacial bonding ability between the polyethylene fiber and the cement matrix and improves the crack resistance, ductility and toughness of the composite material, but also enhances its dispersibility, making the resulting composite material more suitable for the use needs of rail transit engineering repair scenarios.

[0024] Furthermore, before activation, the polyethylene fibers need to be degreased, cleaned, and dried.

[0025] Furthermore, the activation method includes one or more of corona treatment, low-temperature plasma treatment, and ultraviolet ozone treatment.

[0026] In this invention, as an example, low-temperature plasma treatment is used for activation. The low-temperature plasma treatment uses air as the working gas, with a treatment power of 100W-300W, a treatment time of 30s-180s, and a treatment distance of 5mm-15mm.

[0027] Furthermore, the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water evenly, with the volume fraction of anhydrous ethanol being 80%-90%.

[0028] Furthermore, the silane coupling agent having hydroxyl and amino groups includes γ-aminopropyltriethoxysilane.

[0029] Furthermore, the polyethylene fiber has a diameter of 22μm-24μm and a length of 8mm-12mm.

[0030] Furthermore, the activated polyethylene fiber has a mass fraction of 5%-10% in an ethanol aqueous solution containing a silane coupling agent.

[0031] Furthermore, the retarder is tartaric acid.

[0032] Furthermore, the thickener is hydroxypropyl methylcellulose ether.

[0033] Furthermore, the polyether-modified silicone defoamer is Sihai E-550 industrial defoamer (Hubei Longsheng Sihai New Materials Co., Ltd.).

[0034] Furthermore, the water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent.

[0035] Furthermore, the polycarboxylate superplasticizer is P535 polycarboxylate superplasticizer (Jiangsu Ningbao Materials Technology Co., Ltd.).

[0036] Furthermore, the shrinkage reducing agent is TenSil P80 high-efficiency shrinkage reducing agent (Celeconi).

[0037] Furthermore, the expanding agent is a ettringite free calcium oxide composite expanding agent, abbreviated as HP-CSA expanding agent (Denka Co., Ltd.).

[0038] Furthermore, the cement-based composite material includes sulfoaluminate cement with a strength grade of 52.5, ordinary silicate cement with a strength grade of 42.5, grade 1 fly ash, isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand (Yinan Yunlong Silica Sand Co., Ltd.), γ-aminopropyltriethoxysilane modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate superplasticizer, and TenSilP. 80 high-efficiency shrinkage reducing agent, ettringite free calcium oxide composite expansion agent, by weight, the aforementioned sulfoaluminate cement with a strength grade of 52.5, ordinary silicate cement with a strength grade of 42.5, grade 1 fly ash, isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate high-efficiency water-reducing agent, TenSil The ratio of P80 high-efficiency shrinkage reducer to ettringite free calcium oxide composite expansion agent is (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 parts): (2.4-2.6 parts): (5.4-5.6 parts): (8-12 parts): (68-72 parts).

[0039] Furthermore, the cement-based composite material also includes water, and the ratio of water to sulfoaluminate cement by mass is (320-340 parts):(700-720 parts).

[0040] This invention also provides a method for preparing a rapid-hardening, early-strength, high-ductility cement-based composite material, the method comprising the following steps: S1: Pre-dispersion treatment of modified polyethylene fibers; S2: According to the mass ratio, weigh out the sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite calcium carbonate powder, quartz sand, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expansion agent, and put them into the concrete mixer and dry mix for 2 minutes. S3: Add the weighed water into the mixer all at once and mix for 2-3 minutes; S4: Add the pre-dispersed modified fiber evenly to the mixer within 3-4 minutes; S5: Continue stirring for 1 minute; S6: After stirring, transfer the mixture to a mold and cure it at a temperature of (20±2)℃ and a relative humidity of (50±10)% until the required test age. Demolding will then yield the composite material. The modified aragonite-type calcium carbonate powder is a titanate coupling agent modified aragonite-type calcium carbonate powder. The modified fiber is a polyethylene fiber modified with a silane coupling agent containing hydroxyl and amino groups; The modified defoamer is a polyether-modified silicone defoamer.

[0041] This invention also provides the application of fast-hardening, early-strength, and high-ductility cement-based composite materials in the repair of rail transit structures.

[0042] Furthermore, the rail transit structure repair includes the reinforcement and maintenance of the inner wall of the rail transit tunnel, the replacement and repair of the track slab joint material, and the crack-resistant and seepage-proof reinforcement of the drainage ditch inside the section.

[0043] In this invention, the reinforcement and maintenance of the inner wall of a rail transit tunnel specifically involves applying the fast-hardening, early-strength, high-ductility cement-based composite material of this invention by spraying or manual application to address defects such as cracks, surface spalling, and water leakage in the tunnel lining. Due to the application environment of the inner wall of a rail transit tunnel, the repair material needs not only supporting strength but also a certain degree of toughness. Therefore, the composite material of this invention can significantly shorten on-site curing time, reduce tunnel closure operation time, and meet the construction requirements during rail transit maintenance windows. Modification of polyethylene fiber and aragonite-type calcium carbonate powder significantly improves the ductility and crack resistance of the material matrix, effectively inhibiting the further propagation of lining cracks. Simultaneously, the material exhibits high bonding strength with the original concrete lining interface and excellent impermeability, enabling simultaneous structural reinforcement and seepage prevention of the tunnel inner wall.

[0044] In this invention, the replacement and repair of track slab joint materials specifically addresses the problem of aging, cracking, and failure of the original filler material at the joints of ballastless track slabs. The composite material of this invention is used as a replacement filler material for the joints, which can meet operational strength requirements in a short time, satisfying the operational needs of rapid construction and opening within track maintenance windows. The material's high ductility and deformation coordination can adapt to the temperature expansion and contraction deformation of the track slab and the dynamic displacement under train dynamic loads, preventing cracking and damage at the joints. It also possesses excellent fatigue resistance, extending the service life of the track slab joints.

[0045] In this invention, the crack-resistant and seepage-proof reinforcement of the drainage ditch inside the rail transit section specifically involves: addressing cracks and leaks in the inner wall of the drainage ditch using the composite material of this invention for overall or partial repair. This material, with its excellent high ductility, can effectively resist cracking of the drainage ditch caused by uneven foundation settlement and temperature stress; simultaneously, the crack-resistant effect of the modified fibers synergistically works with the dense structure of the matrix to significantly improve the material's seepage resistance, thereby achieving a dual reinforcement effect of crack resistance and seepage prevention for the drainage ditch structure.

[0046] Furthermore, during the application process, the cement-based composite material exhibits a 2-hour compressive strength ≥22MPa and a 28-day compressive strength ≥60MPa.

[0047] The embodiments of the present invention have the following technical effects: 1. This invention employs a composite cementitious system composed of rapid-hardening sulfoaluminate cement and ordinary silicate cement as the main source of strength development for repair materials. Sulfoaluminate cement undergoes rapid hydration, forming hydration products such as ettringite earlier, which is beneficial for rapidly establishing early strength. Ordinary silicate cement hydrates to form hydrated calcium silicate gel and calcium hydroxide, which can continuously participate in structural formation and strength development in the mid-to-late stages. The combination of the two is beneficial for balancing the early strength and later strength stability of the material. Fly ash is used to optimize particle size distribution, improve the workability of the paste, and enhance the microstructure of the hardened body, balancing workability and early strength development under controlled dosage conditions. Aragonite-type calcium carbonate powder promotes matrix densification through micro-filling, heterogeneous nucleation, and particle size optimization. Its needle-like or rod-like particles can also inhibit and deflect crack propagation. After modification with a titanate coupling agent, the dispersibility and interfacial compatibility of aragonite-type calcium carbonate powder with cement paste are improved, which is beneficial for its uniform distribution and full utilization of micro-filling and nucleation effects. After surface activation and silane coupling modification, polyethylene fibers exhibit increased surface polarity and hydrophilicity, which improves fiber wetting, dispersion, and interfacial adhesion in cementitious slurries. This allows the fibers to exert energy-dissipating effects through cross-slit bridging, pull-out slip, and tensile deformation. Polyether-modified silicone defoamers, through the low surface tension of silicone segments and the aqueous dispersion effect of polyether segments, break and suppress bubbles formed during mixing, reducing macropores and interconnected pore defects in the hardened body and improving matrix density.

[0048] In this invention, the modified aragonite-type calcium carbonate powder, modified polyethylene fiber, and polyether-modified silicone defoamer do not function independently, but rather synergistically regulate the composite material at three scales: particle-slurry interface, fiber-matrix interface, and pore structure. The modified aragonite-type calcium carbonate powder improves the dispersion of fine particles and promotes the nucleation of hydration products, resulting in refined matrix pores and a denser structure, providing a more continuous and dense matrix and a stable anchoring environment for the modified polyethylene fiber. The modified polyethylene fiber acts as a cross-crack bridging agent after matrix cracking, inhibiting crack propagation and dissipating fracture energy. Its surface polar groups enhance the interfacial interaction with the modified aragonite-type calcium carbonate powder and cement hydration products, promoting the synergistic effect of particle crack inhibition and fiber bridging mechanisms. The polyether-modified silicone defoamer reduces the number of harmful pores and interconnected pores, increasing matrix density and interfacial continuity, thereby further improving the filling and nucleation effects of the modified aragonite-type calcium carbonate powder, as well as the interfacial bonding and stress transfer efficiency of the modified polyethylene fiber. Thus, the three components form a multi-scale synergistic reinforcement mechanism that promotes mutual reinforcement through "particle microstructure optimization, pore structure regulation, and fiber bridging toughening": modified aragonite calcium carbonate powder and polyether-modified silicone defoamer jointly improve matrix density and fiber anchoring environment; modified polyethylene fibers further bridge and dissipate energy in microcracks formed within the matrix; and fibers and needle-like or rod-shaped aragonite calcium carbonate particles can jointly hinder crack propagation through bridging, pull-out, crack deflection, and passivation mechanisms, respectively. Therefore, the three modified components are coupled and mutually reinforcing at different scales, forming a continuous regulation system from microporous structure and particle interface to macroscopic crack propagation. Compared to using any one modified component alone, this system can more fully exert the effects of densification reinforcement, interface reinforcement, and toughness enhancement, thereby simultaneously improving the early and late mechanical properties, crack resistance, flexural strength, interfacial bonding properties, and durability of the composite material, as well as enhancing the material's volume stability and freeze-thaw resistance.

[0049] Furthermore, a dual-blending strategy of shrinkage-reducing agent and HP-CSA expansive agent is adopted. The shrinkage-reducing agent reduces capillary shrinkage stress by lowering the surface tension of the pore solution; the HP-CSA expansive agent hydrates to generate ettringite, resulting in moderate volume expansion to compensate for the self-shrinkage and drying shrinkage of the matrix. The synergistic effect of the two ensures that the 28-day shrinkage rate of the material meets the requirements of the aforementioned maintenance rules. This invention incorporates tartaric acid as a retarder, whose carboxyl groups can complex with calcium ions, delaying the formation rate of ettringite in sulfoaluminate cement and controlling the initial setting time to ≥20 minutes, meeting the requirement of ≥20 minutes of workable time in "Repair Mortar for High-Speed ​​Railway Concrete Structures" (Q / CR 659-2018), thus taking into account early strength while meeting the specified initial setting time.

[0050] 2. This invention utilizes the synergistic hydration effect of a composite cementitious system of sulfoaluminate cement and ordinary silicate cement, and introduces aragonite-type calcium carbonate powder to play a role in microfilling, heterogeneous nucleation and interface regulation. Combined with a low-volume fly ash design, the prepared composite material meets the requirements of the "High-Speed ​​Railway Line Maintenance Rules" (Tiegongdian

[2023] No. 106) for compressive strength, flexural strength, bond strength, alkali resistance, and frost resistance at 2 hours, 1 day, 7 days, and 28 days, thereby achieving a synergistic improvement in mechanical properties and long-term durability.

[0051] 3. This invention, through the rational design of the cementitious material system and fiber content, achieves a relatively low elastic modulus (20-25 GPa, approximately 56%-70% of C55 grade concrete) while ensuring that the material strength performance meets the requirements of the aforementioned maintenance rules. When structural deformation is caused by temperature changes or foundation settlement, the restraint stress generated within the repair layer is small, exhibiting good deformation coordination ability and long-term service reliability. Attached Figure Description

[0052] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0053] Figure 1 This is the four-point bending load-deflection curve of Example 1. The vertical line in the four-point bending load-deflection curve, together with the curve to its left, forms the area under the curve that is 0.85 times the peak load (N·mm), which is the area value in the curve. This area value is used to calculate the equivalent bending toughness (kJ / m²). 3 The key parameters of ).

[0054] Figure 2 This is the four-point bending load-deflection curve of Example 3.

[0055] Figure 3 This is the four-point bending load-deflection curve of Scale 9.

[0056] Figure 4 This is a four-point bending load-deflection curve for scale 10. Detailed Implementation

[0057] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0058] In a first aspect, some embodiments of the present invention provide a rapid-hardening, early-strength, high-ductility cement-based composite material, wherein the cement-based composite material comprises sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expanding agent. By mass, the ratio of the sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expanding agent is (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 parts): (2.4-2.6 parts): (5.4-5.6 portions): (8-12 portions): (68-72 portions); The modified aragonite-type calcium carbonate powder is a titanate coupling agent modified aragonite-type calcium carbonate powder. The modified fiber is a polyethylene fiber modified with a silane coupling agent containing hydroxyl and amino groups; The modified defoamer is a polyether-modified silicone defoamer.

[0059] In this invention, surface-modified polyethylene fibers, surface-modified aragonite-type calcium carbonate powder, and polyether-modified silicone defoamer synergistically regulate the composite material at three scales: particle-slurry interface, fiber-matrix interface, and pore structure. The modified aragonite-type calcium carbonate powder improves the dispersion of fine particles and promotes the nucleation of hydration products, resulting in refined matrix pores and a denser structure, providing a more continuous and dense matrix and a stable anchoring environment for the modified polyethylene fibers. The modified polyethylene fibers then act as a cross-crack bridging agent after matrix cracking, inhibiting crack propagation and dissipating fracture energy. Their surface polar groups enhance the interfacial interaction with the modified aragonite-type calcium carbonate powder and cement hydration products, promoting the synergistic effect of particle crack inhibition and fiber bridging mechanisms. The polyether-modified silicone defoamer reduces the number of harmful pores and interconnected pores, increasing matrix density and interfacial continuity, thereby further improving the filling and nucleation effect of the modified aragonite-type calcium carbonate powder and the interfacial bonding and stress transfer efficiency of the modified polyethylene fibers. Thus, the three components form a multi-scale synergistic reinforcement mechanism that promotes mutual reinforcement through "particle microstructure optimization, pore structure regulation, and fiber bridging toughening": modified aragonite calcium carbonate powder and polyether-modified silicone defoamer jointly improve matrix density and fiber anchoring environment; modified polyethylene fibers further bridge and dissipate energy in microcracks formed within the matrix; and fibers and needle-like or rod-shaped aragonite calcium carbonate particles can jointly hinder crack propagation through bridging, pull-out, crack deflection, and passivation mechanisms, respectively. Therefore, the three modified components are coupled and mutually reinforcing at different scales, forming a continuous regulation system from microporous structure and particle interface to macroscopic crack propagation. Compared to using any one modified component alone, this system can more fully exert the effects of densification reinforcement, interface reinforcement, and toughness enhancement, thereby simultaneously improving the early and late mechanical properties, crack resistance, flexural strength, interfacial bonding properties, and durability of the composite material, as well as enhancing the material's volume stability and freeze-thaw resistance.

[0060] In some embodiments, the sulfoaluminate cement is a rapid-hardening sulfoaluminate cement with a strength grade of 52.5.

[0061] In some embodiments, the ordinary silicate cement is ordinary silicate cement with a strength grade of 42.5 or 52.5.

[0062] In some embodiments, the fly ash is Class I fly ash.

[0063] In some embodiments, the preparation method of the titanate coupling agent modified aragonite calcium carbonate powder is as follows: aragonite calcium carbonate powder with a water content of less than 0.5% is added to an ethanol solution to prepare a slurry with a solid content of 40%-60%; anhydrous ethanol containing titanate coupling agent is added to the slurry and mixed evenly; the mixture is stirred for 30-90 minutes at 40℃-60℃ and a rotation speed of 1000-3000 r / min; the mixture is dried at 80℃-110℃, depolymerized, and sieved to obtain the titanate coupling agent modified aragonite calcium carbonate powder.

[0064] In some embodiments, aragonite calcium carbonate powder with a moisture content of less than 0.5% can be obtained by drying aragonite calcium carbonate powder at 80°C-110°C, or by purchasing aragonite calcium carbonate powder with a moisture content of less than 0.5%.

[0065] In some embodiments, the ethanol solution is a mixed solvent composed of anhydrous ethanol and deionized water, with the ratio of anhydrous ethanol to deionized water being (4-9):1 by volume.

[0066] In some embodiments, the ratio of the titanate coupling agent to anhydrous ethanol is 1:(5-10) by mass.

[0067] In some embodiments, the mass ratio of the titanate coupling agent to aragonite-type calcium carbonate powder is 1%.

[0068] In some embodiments, the titanate coupling agent includes one or more of isopropyl tris(dioctylphosphoyloxy) titanate and isopropyl tris(dioctylphosphoyloxy) titanate.

[0069] In some embodiments, the aragonite-type calcium carbonate powder has a CaCO3 content of ≥95%, an average particle size of 5μm-15μm, a specific surface area of ​​≥500m² / kg, and its crystal structure retains the characteristics of aragonite-type calcium carbonate. The particle morphology is preferably needle-shaped or rod-shaped.

[0070] This invention improves the dispersion state of fine particles and the particle-slurry interface by surface-modified aragonite-type calcium carbonate powder, allowing the micro-filling and heterogeneous nucleation effects to be more fully utilized, which is beneficial to improving the matrix density and mechanical strength. Simultaneously, the needle-like or rod-shaped high aspect ratio morphology of aragonite-type calcium carbonate can create certain crack-inhibiting, deflecting, and passivating effects during crack propagation; the interfacial layer formed by the titanate coupling agent can also improve the interfacial compatibility between aragonite particles and cement hydration products, reducing micro-defects caused by particle agglomeration. These effects, combined with the bridging and pull-out energy dissipation mechanism of modified polyethylene fibers, are beneficial to improving the crack resistance and deformation capacity of the composite material.

[0071] In some embodiments, the quartz sand is quartz sand with a particle size of 100-170 mesh.

[0072] In some embodiments, the preparation method of the silane coupling agent modified polyethylene fiber with hydroxyl and amino groups is as follows: the surface of the polyethylene fiber is activated, and the activated polyethylene fiber is immersed in an ethanol aqueous solution containing a silane coupling agent, wherein the mass concentration of the silane coupling agent in the ethanol aqueous solution is 1%-5%; the pH value of the system is adjusted to 4-5 with acetic acid, and the fiber is allowed to stand for hydrolysis for 20-60 minutes, followed by immersion at 20℃-40℃ for 30-120 minutes, during which stirring is required; the fiber is then washed with anhydrous ethanol and deionized water in sequence, and dried at 50℃-80℃.

[0073] In some embodiments, the polyethylene fibers need to be degreased, cleaned, and dried before activation.

[0074] In some embodiments, the activation method includes one or more of corona treatment, low-temperature plasma treatment, and ultraviolet ozone treatment.

[0075] In some embodiments, the ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water evenly, with the volume fraction of anhydrous ethanol being 80%-90%.

[0076] This invention utilizes surface-activated and coupling-modified polyethylene fibers to enhance fiber surface hydrophilicity and interfacial interaction. Combined with a fiber pre-dispersion process, this facilitates uniform dispersion and stable bridging of the fibers under short-term mixing conditions, thereby improving the material's crack resistance, flexural strength, and ductility. Specifically, after surface activation and silane coupling modification, the number of polar and silanol groups on the polyethylene fiber surface increases, improving the wettability between the fiber and cement paste and enhancing the interfacial bond between the fiber and the cement matrix. Under external loads, when cracks in the cement matrix extend to the fibers, the fibers can bear part of the tensile stress through cross-crack bridging and dissipate fracture energy through mechanisms such as fiber pull-out, interfacial friction slip, and fiber self-stretching. This inhibits crack width growth and crack penetration, improving the material's crack resistance, flexural strength, tensile strength, and deformation capacity. Simultaneously, appropriate interfacial bond strength helps achieve a balance between "effective stress transfer" and "controllable pull-out energy dissipation," preventing premature fiber debonding or brittle fracture due to excessive interfacial bond strength.

[0077] In some embodiments, the silane coupling agent having hydroxyl and amino groups includes γ-aminopropyltriethoxysilane.

[0078] In some embodiments, the polyethylene fiber has a diameter of 22μm-24μm and a length of 8mm-12mm.

[0079] In some embodiments, the retarder is tartaric acid.

[0080] In some embodiments, the thickener is hydroxypropyl methylcellulose ether.

[0081] In some embodiments, the polyether-modified silicone defoamer is Sihai E-550 industrial defoamer.

[0082] This invention employs a polyether-modified silicone defoamer to regulate harmful air bubbles in freshly mixed slurry, forming a synergistic effect of "fiber interface—particle interface—pore structure" with surface-modified polyethylene fiber and surface-modified aragonite-type calcium carbonate powder. The polyether-modified silicone defoamer utilizes the lower surface tension of the silicone component to promote bubble film rupture and improves dispersion and persistence in the aqueous slurry using polyether segments, thereby reducing the stability of entrained air bubbles during mixing, minimizing harmful macropores and interconnected pore defects in the hardened body, and improving matrix density and interfacial continuity. Surface-modified aragonite-type calcium carbonate powder, through micro-filling, gradation optimization, and heterogeneous nucleation, helps refine the pore structure and improve the particle-slurry interface. Surface-modified polyethylene fiber promotes uniform dispersion and crack bridging by improving wetting and interfacial adhesion. At appropriate dosages, all three components collectively contribute to improving matrix density, interfacial integrity, crack resistance, and durability.

[0083] In some embodiments, the water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent.

[0084] In some embodiments, the polycarboxylate superplasticizer is P535 polycarboxylate superplasticizer (Jiangsu Ningbao Materials Technology Co., Ltd.).

[0085] In some embodiments, the shrinkage reducing agent is TenSil P80 high-efficiency shrinkage reducing agent (Celeconi).

[0086] In some embodiments, the expanding agent is a ettringite free calcium oxide composite expanding agent, abbreviated as HP-CSA expanding agent (Denka Co., Ltd.).

[0087] In some embodiments, the cement-based composite material includes sulfoaluminate cement with a strength grade of 52.5, ordinary Portland cement with a strength grade of 42.5, grade I fly ash, isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane-modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate superplasticizer, and TenSil. The proportions of P80 high-efficiency shrinkage reducing agent, ettringite free calcium oxide composite expansion agent, and, by weight, 52.5 strength grade sulfoaluminate cement, 42.5 strength grade ordinary silicate cement, grade 1 fly ash, isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate high-efficiency water-reducing agent, TenSil P80 high-efficiency shrinkage reducing agent, and ettringite free calcium oxide composite expansion agent are (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 portions): (2.4-2.6 portions): (5.4-5.6 portions): (8-12 portions): (68-72 portions).

[0088] In some embodiments, the cement-based composite material further includes water, wherein the ratio of water to sulfoaluminate cement by mass is (320-340 parts):(700-720 parts).

[0089] Secondly, some embodiments of the present invention also provide a method for preparing a rapid-hardening, early-strength, high-ductility cement-based composite material, the steps of which include: S1: Pre-dispersion treatment of modified polyethylene fibers; S2: According to the mass ratio, weigh out the sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite calcium carbonate powder, quartz sand, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expansion agent, and put them into the concrete mixer and dry mix for 2 minutes. S3: Add the weighed water into the mixer all at once and mix for 2-3 minutes; S4: Add the pre-dispersed modified fiber evenly to the mixer within 3-4 minutes; S5: Continue stirring for 1 minute; S6: After stirring, transfer the mixture to a mold and cure it at a temperature of (20±2)℃ and a relative humidity of (50±10)% until the required test age. Demolding will then yield the composite material. The modified aragonite-type calcium carbonate powder is a titanate coupling agent modified aragonite-type calcium carbonate powder. The modified fiber is a polyethylene fiber modified with a silane coupling agent containing hydroxyl and amino groups; The modified defoamer is a polyether-modified silicone defoamer.

[0090] In the method of this invention, polyethylene fibers, due to their hydrophobicity, exhibit poor compatibility with other materials in the composite material, especially cement. Therefore, in this invention, a silane coupling agent containing hydroxyl and amino groups is used to modify the polyethylene fibers. The hydrophilicity of the modified polyethylene fibers is significantly improved. However, considering the application environment of the composite material, to ensure uniform dispersion and thus better support strength and toughness of the subsequent repair structure, the modified polyethylene fibers are pre-dispersed in this invention, which improves the uniformity of dispersion of the composite material later.

[0091] Thirdly, some embodiments of the present invention also provide the application of fast-hardening, early-strength, high-ductility cement-based composite materials in the repair of rail transit structures.

[0092] In some embodiments, the rail transit structure repair includes reinforcement and maintenance of the inner wall of the rail transit tunnel, replacement and repair of track slab joint materials, and crack-resistant and seepage-proof reinforcement of the drainage ditch inside the section.

[0093] In some embodiments, during the application process, the cement-based composite material has a 2-hour compressive strength of ≥22MPa and a 28-day compressive strength of ≥60MPa.

[0094] The following description, in conjunction with specific embodiments and comparative examples, illustrates the points: Example 1: This embodiment describes a rapid-hardening, early-strength, high-ductility cement-based composite material for repairing rail transit structures. The raw materials, by weight, include: 330 parts water; 710 parts rapid-hardening sulfoaluminate cement with a strength grade of 52.5; 300 parts ordinary Portland cement with a strength grade of 42.5; 220 parts grade I fly ash; and 30 parts isopropyltris(dioctylphosphoyloxy)titanate-modified aragonite-type calcium carbonate powder (wherein the aragonite-type calcium carbonate powder has a CaCO3 content ≥95%, an average particle size of 10 μm, and a specific surface area of ​​600 m²). 2 / kg, with a rod-shaped crystal structure); 440 parts 100-170 mesh quartz sand (Yinan Yunlong Silica Sand Co., Ltd.); 9 parts γ-aminopropyltriethoxysilane modified polyethylene fiber; 2 parts tartaric acid; 0.3 parts hydroxypropyl methylcellulose ether; 2.5 parts Sihai E-550 industrial defoamer; 5.5 parts P535 polycarboxylate high-efficiency water-reducing agent (Jiangsu Ningbao Materials Technology Co., Ltd.); 10 parts TenSil P80 high-efficiency shrinkage reducer (Celeconi); 70 parts ettringite free calcium oxide composite expansion agent, abbreviated as HP-CSA expansion agent (Denka Co., Ltd.).

[0095] Preparation method of isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite calcium carbonate powder: Aragonite calcium carbonate powder is dried at 100℃ to a moisture content ≤0.5%, cooled, and then added to a mixed solvent of anhydrous ethanol and water (the volume ratio of anhydrous ethanol to water is 6:1) to prepare a slurry with a solid content of 50%; isopropyl tris(dioctylphosphoyloxy)titanate is pre-diluted with anhydrous ethanol and added to the above slurry (the mass ratio of isopropyl tris(dioctylphosphoyloxy)titanate to anhydrous ethanol is 1:7), and the amount of isopropyl tris(dioctylphosphoyloxy)titanate added is 1% of the mass of aragonite calcium carbonate powder. The mixture is stirred at high speed at 60℃ and 2000 r / min for 50 min; dried at 100℃, depolymerized, and sieved to obtain isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite calcium carbonate powder.

[0096] Preparation method of γ-aminopropyltriethoxysilane modified polyethylene fiber: First, the polyethylene fiber is degreased, cleaned and dried, and then surface activated by low-temperature plasma treatment (the low-temperature plasma treatment uses air as the working gas, the treatment power is 200W, the treatment time is 100s, and the treatment distance is 10mm); the activated polyethylene fiber is immersed in a mixed solution of ethanol and water containing γ-aminopropyltriethoxysilane (where the volume fraction of anhydrous ethanol in the ethanol aqueous solution is 80%), the mass concentration of γ-aminopropyltriethoxysilane is 3%, the pH is adjusted to 5 with acetic acid, and the solution is allowed to stand for hydrolysis for 40min; then it is immersed at 40℃ for 100min and stirred to allow γ-aminopropyltriethoxysilane to be adsorbed and condensed on the fiber surface; after removal, it is washed with anhydrous ethanol and deionized water in sequence, and dried at 70℃ to obtain γ-aminopropyltriethoxysilane modified polyethylene fiber, wherein the mass fraction of the activated polyethylene fiber in the ethanol aqueous solution containing silane coupling agent is 5%.

[0097] A method for preparing a fast-hardening, early-strength, high-ductility cement-based composite material for repairing rail transit structures includes the following steps: S1: Pre-dispersion treatment of modified polyethylene fibers; S2: According to the mass ratio, weigh out the sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite calcium carbonate powder, quartz sand, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expansion agent, and put them into the concrete mixer and dry mix for 2 minutes. S3: Add the weighed water into the mixer all at once and mix for 2-3 minutes; S4: Add the pre-dispersed modified fiber evenly to the mixer within 3-4 minutes; S5: Continue stirring for 1 minute; S6: After stirring, transfer the mixture to a mold and cure it at a temperature of (20±2)℃ and a relative humidity of (50±10)% until the required test age. Demolding will then yield the composite material.

[0098] Example 2: This example is a fast-hardening, early-strength, high-ductility cement-based composite material for repairing rail transit structures. The difference from Example 1 is that ordinary Portland cement with a strength grade of 52.5 is used to completely replace ordinary Portland cement with a strength grade of 42.5. The other raw materials and preparation methods are the same as in Example 1.

[0099] Example 3: This example describes a fast-hardening, early-strength, and high-ductility cement-based composite material for repairing rail transit structures. The difference from Example 1 is that the amount of γ-aminopropyltriethoxysilane-modified polyethylene fiber is increased to 15 parts. The remaining raw materials and preparation methods are the same as in Example 1.

[0100] Example 4: This example describes a fast-hardening, early-strength, and high-ductility cement-based composite material for repairing rail transit structures. The difference from Example 1 is that the amount of isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite calcium carbonate powder is reduced, while the amount of fly ash is increased. The total mass of fly ash and isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite calcium carbonate powder remains unchanged, i.e., 230 parts fly ash and 20 parts isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite calcium carbonate powder. All other raw materials and preparation methods are the same as in Example 1.

[0101] Example 5: This example describes a fast-hardening, early-strength, high-ductility cement-based composite material for repairing rail transit structures. The difference from Example 1 is that the amount of isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite calcium carbonate powder is increased, while the amount of fly ash is decreased. The total mass of fly ash and isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite calcium carbonate powder remains unchanged, i.e., 200 parts fly ash and 50 parts isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite calcium carbonate powder. All other raw materials and preparation methods are the same as in Example 1.

[0102] Comparative Example 1: The difference from Example 1 is that 1010 parts of sulfoaluminate cement and 0 parts of ordinary silicate cement were used, while the other raw materials and preparation methods were the same as in Example 1.

[0103] Comparative Example 2: The difference from Example 1 is that 610 parts of sulfoaluminate cement and 400 parts of ordinary silicate cement were used, while the other raw materials and preparation methods were the same as in Example 1.

[0104] Comparative Example 3: The difference from Example 1 is that the amount of fly ash is increased, namely 620 parts of sulfoaluminate cement, 260 parts of ordinary silicate cement, 350 parts of fly ash, and 30 parts of isopropyltris(dioctylphosphoyloxy)titanate modified aragonite calcium carbonate powder. The remaining raw materials and preparation methods are the same as in Example 1.

[0105] Comparative Example 4: The difference from Example 1 is that 250 parts of fly ash and 0 parts of isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder were used, while the other raw materials and preparation methods were the same as in Example 1.

[0106] Comparative Example 5: The difference from Example 1 is that the amount of tartaric acid was adjusted to 1.6 parts, while the other raw materials and preparation methods were the same as in Example 1.

[0107] Comparative Example 6: The difference from Example 1 is that stearic acid (Coconut Palm PALMAC 98-18 industrial grade high-purity stearic acid) modified aragonite calcium carbonate powder is used instead of isopropyl tris(dioctylphosphoyloxy) titanate modified aragonite calcium carbonate powder; the amount of stearic acid added is 1% of the mass of aragonite calcium carbonate powder, and the remaining raw materials and preparation methods are the same as in Example 1.

[0108] Comparative Example 7: The difference from Example 1 is that γ-glycidoxypropyltrimethoxysilane modified polyethylene fiber is used instead of γ-aminopropyltriethoxysilane modified polyethylene fiber. The surface activation and coupling modification process of γ-glycidoxypropyltrimethoxysilane modified polyethylene fiber is the same as in Example 1, and the other raw materials and preparation methods are the same as in Example 1.

[0109] Comparative Example 8: The difference from Example 1 is that THIX-278 silicone defoamer (Yantai Hengxin Chemical Technology Co., Ltd.) was used instead of Sihai E-550 industrial defoamer. All other raw materials and preparation methods are the same as in Example 1.

[0110] Comparative Example 9: A typical formula for existing polymer cement mortar for structural reinforcement was used as a control. The raw materials included, by weight, 150 parts water, 500 parts sulfoaluminate cement, 950 parts quartz sand, 0.8 parts tartaric acid, 1 part THIX-278 silicone defoamer (Yantai Hengxin Chemical Technology Co., Ltd.), 3.75 parts polycarboxylate-based high-efficiency water-reducing agent, and 37.5 parts expansion agent. The sulfoaluminate cement was a rapid-hardening sulfoaluminate cement with a strength grade of 42.5. The preparation method and the source of materials were in accordance with the mixing and curing conditions of Example 1.

[0111] Comparative Example 10: The difference from Example 1 is that unmodified aragonite calcium carbonate powder was used instead of titanate coupling agent modified aragonite calcium carbonate powder; unactivated and silane-coupled polyethylene fiber was used instead of hydroxyl and aminosilane coupling agent modified polyethylene fiber; THIX-278 silicone defoamer (Yantai Hengxin Chemical Technology Co., Ltd.) was used instead of Sihai E-550 industrial defoamer. The remaining raw materials, proportions, and preparation methods are the same as in Example 1.

[0112] The examples and comparative examples were tested: (1) The compressive and flexural strength of the specimens of Examples 1-5, Comparative Examples 1-4, and Comparative Examples 6-10 were tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The size of the compressive specimens was 40mm×40mm×40mm, and the size of the flexural specimens was 40mm×40mm×160mm. The interfacial bond strength of the specimens of Examples 1-5 was tested according to the "Tensile Bond Strength Test" method specified in the "Standard for Test Methods of Basic Performance of Building Mortar" (JGJ / T70). The size of the specimens was 40mm×40mm×10mm. The 28-day shrinkage rate of the specimens of Examples 1-5 was tested according to the "Test Method for Drying Shrinkage of Cement Mortar" (JC / T 603-2004). The size of the specimens was 25mm×25mm×280mm. According to Clause 5.2.7 of "Repair Mortar for High-Speed ​​Railway Concrete Structures" (Q / CR 659-2018), alkali corrosion resistance tests were conducted on the specimens of Examples 1-5, with specimen dimensions of 70mm × 70mm × 20mm. According to the rapid freeze-thaw cycle test in "Standard for Test Methods of Long-Term Performance and Durability of Concrete" (GB / T 50082-2024), freeze-thaw tests were conducted on the specimens of Examples 1-5, and the freeze-thaw resistance was evaluated using relative dynamic modulus of elasticity and mass loss rate; specimen dimensions were 100mm × 100mm × 400mm. According to "Test Methods for Mechanical Properties of High-Ductility Fiber-Reinforced Cementitious Composites" (JC / T 2461-2018), the compressive modulus of elasticity of the specimens of Examples 1-5 was tested; specimen dimensions were 100mm × 100mm × 300mm. According to the Technical Specification for Strengthening Masonry Structures with High-Toughness Concrete (TCECS 997-2022), four-point bending toughness tests were conducted on the specimens of Example 1, Example 3, Comparative Example 9 and Comparative Example 10. The specimen size was 40mm×40mm×160mm.

[0113] (2) The test results are shown in Tables 1-5 below.

[0114] Table 1. Compressive strength test results of the examples and comparative examples. Table 2. Flexural strength test results of the examples and comparative examples. Table 3. Test results of interfacial bond strength in the embodiments Table 4. Test results of shrinkage, alkali resistance, freeze resistance, and elastic modulus of the examples. Table 5. Results of four-point bending toughness tests in the examples and comparative examples. Results analysis: A fast-hardening, early-strength, and high-ductility cement-based composite material was successfully obtained using the method and formulation of this invention. The obtained composite material was tested, and the test results are shown in Tables 1-5.

[0115] In this invention, the composite material is applied to rail transit repair structures. This application scenario requires that the composite material obtained by this invention firstly needs to achieve a certain support strength in a very short time, secondly needs to have a certain toughness to adapt to structural deformation caused by changes in ambient temperature or foundation settlement, and thirdly needs to have good dispersion, because the repair structure is small and uniform dispersion can ensure that the structure is subjected to uniform stress after repair, which is the basis for ensuring the support strength and toughness of the repair structure.

[0116] Therefore, the formulation of the composite material of the present invention was designed, as can be seen from the comparison between Examples 1-5 and Comparative Example 9 in Tables 1-2. Comparative Example 9 is a typical formulation of traditional fast-hardening repair mortar, with high-content sulfoaluminate cement as the single cementitious component. Although it can achieve a 2-hour compressive strength of 31.85 MPa by relying on the rapid hydration of sulfoaluminate, the cementitious system has a single composition, insufficient density of the later hydration products, and lack of continuous hydration effect from active admixtures, resulting in weak strength growth with age. The 28-day compressive strength is only 51.27 MPa, and the 28-day flexural strength is only 10.45 MPa. The later load-bearing capacity and deformation capacity are difficult to meet the long-term service requirements of rail transit structures. This invention employs a composite cementitious system combining rapid-hardening sulfoaluminate cement and ordinary silicate cement: sulfoaluminate cement rapidly hydrates to generate ettringite and hydrated calcium aluminate, providing early strength within 2 hours to meet the rapid opening requirements of nighttime skylight operations; ordinary silicate cement continuously hydrates to generate hydrated calcium silicate gel, which, in conjunction with the secondary hydration reaction of primary fly ash, continuously fills the matrix pores, ensuring stable strength growth and long-term matrix compactness. Furthermore, aragonite-type calcium carbonate powder can simultaneously play a triple role in micro-filling, heterogeneous nucleation, and crack inhibition: fine-grained needle / rod-shaped aragonite particles can fill the micropores between cement particles and hydration products, optimizing particle size distribution and improving matrix density; its high specific surface area provides heterogeneous nucleation sites for hydration products, accelerating early hydration product formation and further enhancing early strength; the high aspect ratio particle morphology can also deflect and passivate microcrack propagation, delaying crack penetration. Polyethylene fibers act as cross-crack bridging agents after the matrix cracks. Through fiber pull-out, interfacial frictional slip, and tensile deformation, they dissipate fracture energy, forming a multi-level toughening system with aragonite-type calcium carbonate powder: "micropore filling - microcrack hindrance - macrocrack bridging," significantly improving the material's flexural strength and deformation capacity. Experimental data show that the 28-day compressive strength of Example 3 is increased by 32% compared to Comparative Example 9, and the 28-day flexural strength is increased by 55%, fully verifying the synergistic advantages of the composite cementitious system and multi-component toughening.

[0117] A comparison of Examples 1-5 with Comparative Example 10 shows that unmodified aragonite-type calcium carbonate powder has low surface energy, is prone to agglomeration, and has poor interfacial compatibility with cement hydration products; unmodified polyethylene fiber has strong surface hydrophobicity, poor dispersion uniformity in cement paste, and weak interfacial adhesion. Both of these factors contribute to a large number of agglomeration defects and weak interfacial areas within the matrix, resulting in a significant decrease in the material's mechanical properties and crack resistance. The 28-day compressive strength of Comparative Example 10 is only 57.16 MPa, and its 28-day flexural strength is only 11.31 MPa, representing decreases of 10.6% and 25.9% respectively compared to Example 1. Its four-point bending equivalent flexural toughness is only 120.00 kJ / m³. Figure 4As shown in Example 1, the toughening effect was significantly weakened, with a 37.0% reduction in toughness. To address this, the present invention employs titanate coupling agents to modify the surface of aragonite-type calcium carbonate powder and silane coupling agents with hydroxyl and amino groups to modify the surface of polyethylene fibers. The modified aragonite-type calcium carbonate powder surface introduces polar organic groups, which improves particle dispersibility in cement paste, reduces agglomeration defects, strengthens the interfacial bonding between particles and hydration products, and reduces weak interfacial areas. The modified polyethylene fiber surface exhibits significantly enhanced hydrophilicity and reactivity, forming a strong interfacial bond with cement hydration products, ensuring effective stress transfer and stable operation of the pull-out energy dissipation mechanism. More importantly, the polar groups on the surface of titanate-modified aragonite particles can form hydrogen bonds and van der Waals forces with the amino and hydroxyl groups of the silane-modified fibers, strengthening the interfacial coupling between inorganic rigid particles and organic flexible fibers. This allows for synergistic action between particle crack resistance and fiber bridging, further enhancing the multi-stage toughening effect.

[0118] Furthermore, titanate-modified aragonite calcium carbonate and aminosilane-modified polyethylene fiber are both active components with surface-grafted organic groups, which can change the solid-liquid interfacial tension of the freshly mixed slurry to a certain extent, thereby improving the stability of the entrained bubble liquid film during mixing. If not controlled, they can easily form harmful macropores and interconnected pores in the hardened matrix, deteriorating the matrix density and weakening the interfacial interaction between particles and fibers. Ordinary polydimethylsiloxane defoamers have poor dispersibility and limited defoaming efficiency in alkaline cement slurry, and may also cause damage to the interfacial modification layer. As shown in the test results of Comparative Example 8, when using ordinary organosilicon defoamers, the 2-hour compressive strength of the material is only 20.31 MPa, and the 28-day compressive strength is only 56.01 MPa, which are 24.7% and 12.4% lower than those in Example 1, respectively. The negative impact of pore structure defects on mechanical properties is very significant. This invention employs a polyether-modified organosilicon defoamer, which combines the high-efficiency defoaming ability of the low surface tension of the organosilicon component with the aqueous phase dispersion stability brought by the polyether segments. On the one hand, it can rapidly reduce the strength of the bubble liquid film, promote the rupture of large bubbles and inhibit the generation of micro bubbles, effectively reduce the porosity of the hardened body, reduce interconnected pore defects, and improve the overall density of the matrix, providing a continuous and dense matrix environment for the micro-filling effect of particles and the stress transfer of fibers. On the other hand, the polyether-modified molecular structure gives it good dispersion compatibility in alkaline cement paste. Within the effective defoaming dosage range, it will not damage the titanate organic-inorganic interface layer on the surface of aragonite calcium carbonate, nor will it over-react with the amino and hydroxyl active sites on the fiber surface, thus fully ensuring the interfacial coupling and synergistic effect between the modified aragonite particles and the modified polyethylene fibers.

[0119] Further verification experiments were conducted based on the application environment, as shown in Table 5. Figures 1-4As shown. In existing technologies, the formulation of Comparative Example 9 is often used for repairs. Comparative Example 9 is a polymer cement mortar commonly used in the field of structural reinforcement. Figure 3 It can be observed that its four-point bending load-deflection curve exhibits typical brittle failure characteristics: there is no drop segment after the load reaches the peak value, proving that the specimen immediately cracks and fails. The deflection corresponding to the peak load is only 0.02 mm, which is much lower than 2.24 mm in Example 1. It can be seen that the repair material obtained by Comparative Example 9 has almost no plastic deformation capacity and toughness reserve, so it is impossible to calculate the area under the curve and the equivalent bending toughness index corresponding to 0.85 times the peak load.

[0120] Based on this, the same experiment was conducted on the composite material of proportion 10, and the results are as follows. Figure 4 As shown. Comparative Example 10 did not employ the multi-component modification technique of this invention. Combined with... Figure 4 As shown in Table 5, the peak load of Comparative Example 10 is 5256.25 N, the corresponding deflection is 1.25 mm, and the equivalent bending toughness is 120 kJ / m. 3 However, all performance indicators were significantly lower than those of Examples 1 and 3, with its equivalent bending toughness being only 63% of that of Example 1. It is evident that the bending toughness of the repair material is significantly improved through the synergistic effect between the composite materials in this invention.

[0121] Example 1 uses the basic formulation system of this invention. Four-point bending test results show that its peak load reaches 5960.23 N, the peak corresponding deflection is 2.24 mm, and the equivalent bending toughness is 190.31 kJ / m³. Figure 1 This meets the requirement of ≥170 kJ / m³ for Grade I (highest grade) high-toughness concrete in the "Technical Specification for High-Toughness Concrete Strengthening Masonry Structures" (TCECS 997-2022). This result confirms that this technical solution can simultaneously and significantly improve the ductility and flexural toughness of the material while achieving rapid hardening and early strength performance. When the content of γ-aminopropyltriethoxysilane-modified polyethylene fiber is increased (Example 3, ...), ... Figure 2 When the load-bearing capacity and deformation toughness of the material are further improved: the peak load increases to 7460.19 N, the peak deflection reaches 2.35 mm, and the equivalent bending toughness increases to 317.47 kJ / m³, which is 166.8% of that in Example 1, far exceeding the threshold value of Grade I high-toughness concrete. Therefore, it can be seen that by appropriately increasing the amount of silane coupling agent modified polyethylene fiber in the material system of this patent, the energy absorption capacity of the material can be effectively enhanced, and the ductility and bending toughness of the repair material can be further optimized.

[0122] Precise control of the retarder dosage is a key technical parameter for achieving a balance between early strength and construction operation time. In Comparative Example 5, when the tartaric acid dosage was reduced to 1.6 parts, the initial setting time of the composite material was only 16 minutes, which did not meet the technical requirement of not less than 20 minutes specified in Article 4.1 of "Repair Mortar for High-Speed ​​Railway Concrete Structures" (Q / CR 659-2018), and could not meet the necessary operation time window for mixing, transportation, and pouring in rail transit repair scenarios. In addition, an excessively rapid hydration process can easily lead to coarse crystals and uneven spatial distribution of hydration products, thereby aggravating internal structural defects in the matrix and hindering the stable development of later mechanical properties. Based on this, the present invention reasonably controls the tartaric acid dosage within the range of 1.8 parts to 2.2 parts. Within this dosage range, the initial setting time of Examples 1 to 5 is not less than 20 minutes, which not only ensures the achievement of early strength performance within 2 hours, but also effectively controls the slurry setting time to adapt to the actual construction rhythm, achieving a synergistic unity between early strength performance and construction operability.

[0123] Based on this, the present invention further investigated the interactions between raw materials modified with different modifying groups. For example, comparing Examples 1-5 with Comparative Examples 6-8, it was found that the supporting strength and flexural strength of the repaired structure obtained by the composite material in the present invention were significantly better than those in Comparative Examples 6-8. It can be observed that when the modifying groups are different, the properties of polyethylene fiber, aragonite calcium carbonate powder, and organosilicon defoamer differ, and their interactions also differ. For example, in Comparative Example 6, stearic acid-modified aragonite calcium carbonate powder was used. After stearic acid modification, the surface of aragonite calcium carbonate mainly consists of long alkyl nonpolar carbon chains with fewer polar groups, resulting in a large loss of hydrogen bond sites. This makes it difficult to form hydrogen bonds with the polyethylene fiber modified by hydroxyl and aminosilane coupling agents, weakening the interfacial coupling between them and the polyethylene fiber, reducing the synergistic effect, and causing a decrease in the flexural strength of the repaired structure. Similarly, the selection of modifying groups for polyethylene fiber and organosilicon defoamer is not a simple substitution, but requires further consideration of their interactions with other substances.

[0124] Finally, experiments were conducted to verify the selection of the raw material ratios in this invention, as shown in the comparisons between Examples 1-5 and Comparative Examples 1-5. When the selected raw material ratios changed, the supporting strength and flexural strength of the repaired structure also changed.

[0125] Interfacial bond strength, shrinkage rate, alkali resistance, freeze-thaw resistance, and elastic modulus were tested for Examples 1-5 of the present invention, and the results are shown in Tables 3 and 4. Table 3 shows that the interfacial bond strengths of Examples 1-5 were 2.25 MPa, 2.38 MPa, 2.16 MPa, 2.03 MPa, and 2.31 MPa, respectively; the interfacial bond strengths after water immersion treatment were 1.83 MPa, 1.96 MPa, 1.71 MPa, 1.64 MPa, and 1.83 MPa, respectively; and the interfacial bond strengths after 25 freeze-thaw cycles were 1.56 MPa, 1.69 MPa, 1.65 MPa, 1.52 MPa, and 1.61 MPa, respectively, all meeting the repair requirements. In particular, Example 2 showed the highest interfacial bond strength among Examples 1-5 under all three working conditions, indicating that using higher-strength ordinary Portland cement is beneficial for further improving the interfacial bearing capacity between the repair material and the substrate. After immersion and freeze-thaw cycles, the interfacial bond strength of each embodiment decreased to some extent, but remained at a high level, indicating that the composite material of the present invention has good interfacial stability and environmental adaptability.

[0126] As shown in Table 4, the 28-day shrinkage rates of Examples 1-5 were 0.018%, 0.022%, 0.017%, 0.013%, and 0.015%, respectively, all lower than the requirement of 0.1%. Furthermore, the shrinkage rates of Examples 4 and 5 were only 0.013% and 0.015%, respectively, demonstrating good volume stability. After alkali resistance testing, Examples 1-5 showed no cracks or peeling, indicating that the material has good alkali resistance stability. After 300 freeze-thaw cycles, the relative dynamic elastic moduli of Examples 1-5 were 86.9%, 90.7%, 86.6%, 88.1%, and 89.3%, respectively, all significantly higher than the requirement of 60%. The mass loss rates were 0.82%, 0.51%, 0.75%, 0.70%, and 0.63%, respectively, all significantly lower than the requirement of 5%, indicating that the material of this invention has good freeze-thaw resistance. Among them, the relative dynamic elastic modulus after freeze-thaw in Example 2 is relatively high, reaching 90.7%, indicating that a reasonable cementitious system and fiber content are beneficial to improving the structural stability of the material under freeze-thaw action.

[0127] The 28-day compressive modulus of elasticity for Examples 1-5 were 23.87 GPa, 24.16 GPa, 22.53 GPa, 22.06 GPa, and 23.06 GPa, respectively, all within the range of 20 GPa-25 GPa. Compared with ordinary high-strength concrete, the material of this invention has a relatively low modulus of elasticity, which is beneficial to improving the deformation coordination between the repair material and the original structure, and reducing the risk of constraint stress and interface delamination caused by deformation incoordination under temperature changes, foundation settlement, and load. Among them, Example 2 has the highest 28-day compressive modulus of elasticity at 24.16 GPa. This is because after replacing 42.5 cement with ordinary Portland cement of strength grade 52.5, the matrix hydration product structure is more compact, and the overall stiffness is slightly improved. Correspondingly, the interfacial bond strength and the relative dynamic modulus of elasticity after freeze-thaw in Example 2 are also at a high level, indicating that a higher strength grade cementitious system is beneficial to improving the matrix compactness and interfacial bearing capacity. Example 3 increased the content of modified polyethylene fiber, resulting in a 28-day compressive modulus of elasticity decreasing to 22.53 GPa, while the 28-day flexural strength increased to 16.18 MPa and the equivalent flexural toughness increased to 317.47 kJ / m³. This indicates that appropriately increasing the content of modified polyethylene fiber can significantly improve the flexural strength and flexural toughness of the material while moderately reducing the matrix elastic modulus, further optimizing the material's deformation coordination and crack resistance. Considering the supporting strength and toughness of the composite material, the composite material of this invention is further preferred, including sulfoaluminate cement with a strength grade of 52.5, ordinary silicate cement with a strength grade of 42.5, grade 1 fly ash, isopropyltris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate high-efficiency water-reducing agent, and TenSil. The proportions of P80 high-efficiency shrinkage reducing agent, ettringite free calcium oxide composite expansion agent, and, by weight, the following components of 52.5 strength grade sulfoaluminate cement, 42.5 strength grade ordinary silicate cement, grade 1 fly ash, isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate high-efficiency water-reducing agent, TenSil P80 high-efficiency shrinkage reducing agent, and ettringite free calcium oxide composite expansion agent are (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 portions): (2.4-2.6 portions): (5.4-5.6 portions): (8-12 portions): (68-72 portions).

[0128] In summary, this invention constructs a multi-component synergistic system consisting of a sulfoaluminate-silicate composite cementing system, titanate-modified aragonite calcium carbonate, silane-modified polyethylene fiber, and polyether-modified organosilicon defoamer. Through a multi-scale synergistic enhancement mechanism of "particle microstructure optimization, pore structure regulation, and fiber bridging toughening," it achieves rapid hardening and early strength characteristics, meets the rapid traffic opening requirements of rail transit track maintenance windows, and simultaneously possesses high ductility and high bending toughness, low elastic modulus deformation coordination, excellent interfacial bonding performance, extremely low shrinkage rate and good volume stability, as well as excellent freeze-thaw resistance, alkali resistance, and other durability properties. It can adapt to the long-term service requirements of various structural repair scenarios such as rail transit tunnel inner wall reinforcement, track slab joint repair, and drainage ditch crack prevention and seepage prevention.

Claims

1. A rapid-hardening, early-strength, high-ductility cement-based composite material, characterized in that, The cement-based composite material comprises sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expanding agent. By mass, the ratio of the sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite-type calcium carbonate powder, quartz sand, modified fiber, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expanding agent is (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 parts): (2.4-2.6 parts): (5.4-5.6 parts): (8-12 parts): (68-72 copies); The modified aragonite-type calcium carbonate powder is a titanate coupling agent modified aragonite-type calcium carbonate powder. The modified fiber is a polyethylene fiber modified with a silane coupling agent containing hydroxyl and amino groups; The modified defoamer is a polyether-modified silicone defoamer.

2. The rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 1, characterized in that, The sulfoaluminate cement is a rapid-hardening sulfoaluminate cement with a strength grade of 52.5; The ordinary Portland cement is ordinary Portland cement with a strength grade of 42.5 or 52.5; The fly ash is Grade I fly ash; The quartz sand is quartz sand with a particle size of 100-170 mesh; The retarder is tartaric acid; The thickener is hydroxypropyl methylcellulose ether; The water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent; The polycarboxylate superplasticizer is P535 polycarboxylate superplasticizer. The shrinkage reducing agent is TenSil P80 high-efficiency shrinkage reducing agent; The expanding agent is a composite expanding agent, and the composite expanding agent is a ettringite free calcium oxide composite expanding agent; The polyether-modified silicone defoamer is Sihai E-550 industrial defoamer; The cement-based composite material also includes water, and the ratio of water to sulfoaluminate cement by mass is (320-340 parts):(700-720 parts).

3. The rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 1, characterized in that, The preparation method of the titanate coupling agent modified aragonite calcium carbonate powder is as follows: aragonite calcium carbonate powder with a water content of less than 0.5% is added to an ethanol solution to prepare a slurry with a solid content of 40%-60%; anhydrous ethanol containing titanate coupling agent is added to the slurry and mixed evenly; the mixture is stirred for 30 min-90 min at 40℃-60℃ and a rotation speed of 1000 r / min-3000 r / min; the mixture is dried at 80℃-110℃, depolymerized, and sieved to obtain the titanate coupling agent modified aragonite calcium carbonate powder.

4. The rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 3, characterized in that, The titanate coupling agent includes one or more of isopropyl tris(dioctylphosphoyloxy) titanate and isopropyl tris(dioctylpyrophosphoyloxy) titanate; The aragonite-type calcium carbonate powder has a CaCO3 content of ≥95%, an average particle size of 5μm-15μm, a specific surface area of ​​≥500m² / kg, and a crystal structure of needle-like or rod-like. The ethanol solution is a mixed solvent composed of anhydrous ethanol and deionized water, wherein the ratio of anhydrous ethanol to deionized water by volume is (4-9):

1. The ratio of the titanate coupling agent to anhydrous ethanol is 1:(5-10) by mass. The mass ratio of the titanate coupling agent to the aragonite-type calcium carbonate powder is 1%.

5. The rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 1, characterized in that, The preparation method of the silane coupling agent modified polyethylene fiber with hydroxyl and amino groups is as follows: the surface of polyethylene fiber is activated, and the activated polyethylene fiber is immersed in an ethanol aqueous solution containing silane coupling agent, the mass concentration of silane coupling agent in the ethanol aqueous solution is 1%-5%; the pH value of the system is adjusted to 4-5 with acetic acid, and the system is allowed to stand for hydrolysis for 20 min-60 min, and then impregnated at 20℃-40℃ for 30 min-120 min. Stirring is required during impregnation. The fiber is then washed with anhydrous ethanol and deionized water in sequence, and dried at 50℃-80℃.

6. The rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 5, characterized in that, The activation method includes one or more of corona treatment, low-temperature plasma treatment, and ultraviolet ozone treatment; The ethanol aqueous solution is prepared by mixing anhydrous ethanol and deionized water evenly, with the volume fraction of anhydrous ethanol being 80%-90%. The silane coupling agent includes γ-aminopropyltriethoxysilane; The polyethylene fibers have a diameter of 22μm-24μm and a length of 8mm-12mm; The activated polyethylene fiber has a mass fraction of 5%-10% in an ethanol aqueous solution containing a silane coupling agent.

7. The rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 1, characterized in that, The cement-based composite material includes sulfoaluminate cement with a strength grade of 52.5, ordinary silicate cement with a strength grade of 42.5, grade I fly ash, isopropyl tris(dioctylphosphoyloxy)titanate-modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane-modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate superplasticizer, and TenSil. The proportions of P80 high-efficiency shrinkage reducing agent, ettringite free calcium oxide composite expansion agent, and, by weight, 52.5 strength grade sulfoaluminate cement, 42.5 strength grade ordinary silicate cement, grade 1 fly ash, isopropyl tris(dioctylphosphoyloxy)titanate modified aragonite-type calcium carbonate powder, 100-170 mesh quartz sand, γ-aminopropyltriethoxysilane modified fiber, tartaric acid, hydroxypropyl methylcellulose ether, Sihai E-550 industrial defoamer, P535 polycarboxylate high-efficiency water-reducing agent, TenSil P80 high-efficiency shrinkage reducing agent, and ettringite free calcium oxide composite expansion agent are (700-720 parts): (290-310 parts): (200-230 parts): (20-50 parts): (430-450 parts): (9-15 parts): (1.8-2.2 parts): (0.28-0.32 portions): (2.4-2.6 portions): (5.4-5.6 portions): (8-12 portions): (68-72 portions).

8. A method for preparing a rapid-hardening, early-strength, high-ductility cement-based composite material, used to prepare the rapid-hardening, early-strength, high-ductility cement-based composite material according to any one of claims 1-7, characterized in that, The preparation method includes the following steps: S1: Pre-dispersion treatment of modified polyethylene fibers; S2: According to the mass ratio, weigh out the sulfoaluminate cement, ordinary silicate cement, fly ash, modified aragonite calcium carbonate powder, quartz sand, retarder, thickener, modified defoamer, water-reducing agent, shrinkage-reducing agent, and expansion agent, and put them into the concrete mixer and dry mix for 2 minutes. S3: Add the weighed water into the mixer all at once and mix for 2-3 minutes; S4: Add the pre-dispersed modified fiber evenly to the mixer within 3-4 minutes; S5: Continue stirring for 1 minute; S6: After stirring, transfer the mixture to a mold and cure it at a temperature of 18℃-22℃ and a relative humidity of 40%-60% until the required test age. Demolding will then yield the composite material. The modified aragonite-type calcium carbonate powder is a titanate coupling agent modified aragonite-type calcium carbonate powder. The modified fiber is a polyethylene fiber modified with a silane coupling agent containing hydroxyl and amino groups; The modified defoamer is a polyether-modified silicone defoamer.

9. The application of the rapid-hardening, early-strength, high-ductility cement-based composite material according to any one of claims 1-7, characterized in that, The fast-hardening, early-strength, and high-ductility cement-based composite material is used for the repair of rail transit structures. The repair of rail transit structures includes the reinforcement and maintenance of the inner wall of rail transit tunnels, the replacement and repair of track slab joint materials, and the crack-resistant and seepage-proof reinforcement of the drainage ditch inside the section.

10. The application of the rapid-hardening, early-strength, high-ductility cement-based composite material according to claim 9, characterized in that, The compressive strength of cement-based composite materials is ≥22MPa after 2 hours and ≥60MPa after 28 days.